Pengaruh Dosis Pupuk NPK Phonska dan Metode Aplikasinya terhadap Indeks Luas Daun Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Tahap Pre-Nursery - Moh. Syahrul Munir; Dewi Puspa Arisandi; Desi Rejeki; Nur Halimah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Oil palm (Elaeis guineensis Jacq.) is one of the world's important commodities as a producer of vegetable oil needed by various industries. Leaf area index is one of the indicators of plant growth seen from the size of the leaf surface area that carries out the photosynthesis process. This study aims to determine the interaction of NPK Phonska fertilizer dose treatment and its application method on the Leaf Area Index of oil palm seedlings at the pre-nursery stage. The study was designed using factorial RAK consisting of 2 factors, namely the dose of NPK Phonska fertilizer (K) and its application method (A), and 3 replications. The K factor consists of 5 levels, namely K0 = 0 g/seedling; K1 = 0.5 g/seedling, K2 = 1 g/seedling, K3 = 1.5 g/seedling, and K4 = 2 g/seedling. Factor A consists of 3 levels, namely A1 = watering, A2 = spreading, and A3 = bag. The observation results were analyzed using analysis of variance and further DMRT test at 5% level if significantly different. The results of the study showed that the dose of NPK Phonska fertilizer 1 g/seedling (K2) gave the highest results on the Leaf Area Index, which was 2.90. The interaction treatment of NPK Phonska fertilizer dose 1 g/seedling and the pocket application method (K2A3) gave the highest results on the parameters of seedling height (12.99 cm) and tuber diameter (1.31 cm). The Leaf Area Index weakened positively on the growth of oil palm seedlings as seen from the height of the seedlings, tuber diameter, and leaf sheath length.